2018
DOI: 10.1177/0143831x18769383
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary framework exploring the role of periodisations in the modern development of a Baltic state: The case of HRM in the Latvian public sector

Abstract: This paper explores the role of 'periodisations' in the development of HRM in the Latvian public sector and consists of a series of 'elite interviews' with leading 'actors' identifying further 'periodisations' which are 'mapped' in an evolutionary framework. Immediately following independence in 1990 was a 'void' period being a time of turmoil. 'Transition' period followed from mid-1990 characterised by up-skilling and the emergence of awareness of HRM. The 'Emergence' period began circa 2008 with more conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Additionally, researchers have increased their emphasis on both organizational strategies and strategic positioning, which have affected the selection of a set of HRM practices. The era of cutthroat competition indicated that effective human resource management (HRM) is no longer content and is executed with a conventional set of practices [14,15] as different researchers indicated the lack of evolutionary research on HRM practices, such as the development of an evolutionary HRM practices-based framework [16], economic evolutionary perspective [17], and lack of integration of national and international HRM standards [18]. Hence, to remain competitive globally, it is important to establish new human resource practices (NHRM).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, researchers have increased their emphasis on both organizational strategies and strategic positioning, which have affected the selection of a set of HRM practices. The era of cutthroat competition indicated that effective human resource management (HRM) is no longer content and is executed with a conventional set of practices [14,15] as different researchers indicated the lack of evolutionary research on HRM practices, such as the development of an evolutionary HRM practices-based framework [16], economic evolutionary perspective [17], and lack of integration of national and international HRM standards [18]. Hence, to remain competitive globally, it is important to establish new human resource practices (NHRM).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their apparent universality they are highly differentiated between cultures (Gueguen et al, 2016). Such is the power and significance of favours in certain societies that they have become discrete concepts, including, for example, the favour-exchanges that occur within Chinese 'Guanxi' (Liu & Jia, 2020), Russian 'Blat' (Cook et al, 2018) and Arabic 'Wasta' (Ali & Weir, 2020).…”
Section: Favourmentioning
confidence: 99%